X-Ray Diffraction and Relativistic Dft Studies on the Molecular Biomarker Fac-Re(Co)3(4,4?-Dimethyl-2,2?-Bpy)(E-2-((3-Amino-Pyridin-4-Ylimino)-Methyl)-4,6-Di-Tert-Butylphenol)(Pf6) - Gacitua-Santalices, M; Gacitua-Santalices, M (Springer International Publishing, 2017)
The fac-[Re(CO)3(4,4′-dimethyl-2,2′-bpy)L]PF6 (C2) complex have been recently reported as a useful fluorophore for walled cells (yeasts and bacteria) without the need of antibodies. In the present work, we report the structural parameters of the C2 complex, where L is an ancillary ligand E-2-((3-amino-pyridin-4-ylimino)-methyl)-4,6-di-tert-butylphenol, which presents an intramolecular hydrogen bond (IHB). The C2 crystals were obtained by slow evaporation of a dichloromethane solution, yielding yellow blocks. The crystal structure solution of the complex C2 showed a monoclinic crystal system and discrete organometallic cations and PF6 - as the counter ion, with partially occupation of solvent molecules (CH2Cl2). The complex C2 having a fac-geometry of the three carbonyl ligands, possesses the following bond distances Re-C(CO): Re1-C24, 1.87(8) Å; Re1-C25, 1.58(12) Å and Re1-C26, 1.90(8) Å. The distorted octahedral geometry observed in the C2 structure is due to the C(CO)-Re1-N1(imine) angle for the three carbonyls that are significantly different. The Re-N1 bond distance of 2.16(4) Å corresponds to the nitrogen coordination of the pyridine fragment of the ancillary ligand L, completing the octahedral geometry. Here we complement the C2 descriptions due to the considerable biological interest of its use as d6 metal fluorophore in walled cells (i.e., yeast and bacteria). DFT calculations were performed including scalar and spin-orbit (SO) relativistic effects with agree often reasonably well with experimental X-ray data. Through frequency calculations we estimated the strength of the intramolecular hydrogen bond (with a OH···N distance of 2.621 Å) accounting for near 40 kcal/mol, indicating that is a strong hydrogen bond which contributes to the molecular stability. In addition, we observed the L electron-withdrawing effect on the rhenium core. The agreement between the observed and computed bond distances and angles brings confidence on the choice of the computed models and level of theory. These kind of Rhenium (I) complexes designed to develop novel fluorophores suitable for biological applications. © 2017 Institute of Chemistry, Slovak Academy of Sciences.